Nilai-nilai Multikultural dalam Pendidikan Islam - Moh. Syamsi (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2019)
Indonesia consists of diverse tribes, customs, religions, languages and cultures. This condition is one side is an invaluable treasure, on other hand it can be counter-productive if it is not managed properly, it is very potential to cause clashes, conflicts and divisions. The emergence of radicalism which is felt lately is worrying. Conflicts in several regions indicate that Indonesian population lacks broad insight into cultural plurality. Therefore, there needs to be a deep understanding of mutual respect between ethnicities, races, groups, customs and religions. Understanding multiculturalism, as a socio-intellectual movement that carries values and principles of difference and emphasizes importance of respecting different cultures. As for planting values of diversity, the most effective is through the world of education, by instilling multicultural values to respond to cultural diversity that has been not yet bridged optimally, by changing form monocultural perspective education that is full of prejudice and discriminatory towards multicultural perspective. This is to create harmony between people with differences that are definitely happening. In fact, the core values ??of multicultural education have similarities with core values contained in Islamic teachings related to hablun minannas. In other words, Islamic teachings in general have contained principles put forward in multicultural education.